REPRESENTASI DIPLOMASI PUBLIK INDONESIA MELALUI CULTURAL EXCHANGE SEBAGAI SARANA KERJASAMA BUDAYA DI KOREA SELATAN - Ratnanggana, Putu Dea Ranudhara; Sushanti, Sukma; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2022)
Representation of Indonesian Public Diplomacy Through Cultural Exchange as a Means of Cultural Cooperation in South Korea This research aims to describes how cultural exchange program as part of Indonesian public diplomacy to introduce Indonesian culture in South Korea by using qualitative method. Researcher uses two main concepts, which are bilateral cooperation and public diplomacy in order to answer the application of cultural exchange as part of public diplomacy instrument for Indonesian culture cooperation in South Korea. This research perceives that cultural exchange program can be used as cooperative relations between two countries through the public diplomacy which can be implented by the government and by the non-government actors. Keywords: Cultural Exchange, Bilateral Cooperation, Public Diplomacy